Seat cushion

By using polyurethane foam seat cushions made of polyols and isocyanate compositions, the problem of insufficient riding comfort in the prior art is solved, and good bending and durability is achieved, and it is suitable for vehicles, ships, and aircraft.

CN119325351APending Publication Date: 2025-01-17INOAC CORP

Patent Information

Application Number
CN202380045478.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-09
Filing Date
2023-05-19
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing seat cushions are difficult to improve riding comfort, especially in terms of bending and not easily feeling touch-touch and durability.

Method used

Using polyurethane foam made of polyol and isocyanate compositions, a multi-layered seat cushion is made by adjusting the composition and structure of the composition, such as in the alkylene oxide unit content, isocyanate index and crosslinking agent ratio, to Meet specific Asker F hardness ratios and other performance indicators.

Benefits of technology

It improves the flexibility of the seat cushion and does not easily feel the touch, enhances riding comfort, and performs excellently in maintaining the durability of the seating posture, and can achieve lightweight and cost reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325351A_ABST
    Figure CN119325351A_ABST
Patent Text Reader

Abstract

The seat cushion (110) is made of polyurethane foam obtained from a composition containing a polyol and an isocyanate. The seat cushion (110) has a compression deflection coefficient of 2.8 or less as measured according to the JISK6400-2 (2012 edition) E method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a seat pad.

[0002] This application claims the benefits of priority based on Japanese Patent Application No. 2022-108852 filed on July 6, 2022 and Japanese Patent Application No. 2022-179573 filed on November 9, 2022, and the entire contents of these patent applications are incorporated into this specification by reference. Background Art

[0003] Patent Documents 1 and 2 describe seat cushioning materials using polyether polyol (PPG).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-107933

[0007] Patent Document 2: Japanese Patent Application Publication No. 2022-039004 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] Seat cushions used in vehicles such as automobiles, ships, and airplanes are required to provide improved riding comfort. Examples of riding comfort include good curvature and a less likely feeling of contact with the ground, durability for maintaining the seat occupant's posture, and surface softness that provides a good tactile feel when the seat occupant is seated. However, it is difficult to sufficiently improve riding comfort with existing seat cushions.

[0010] The present disclosure has been made in view of the above circumstances, and an object of the present invention is to improve the riding comfort of a seat pad by improving at least one of good bending, less likely to feel the ground contact feeling, durability, and surface softness.

[0011] The present disclosure can be implemented in the following ways.

[0012] Means used to solve problems

[0013] <First Method>

[0014] (1) A seat cushion made of a polyurethane foam obtained from a composition containing a polyol and an isocyanate, wherein:

[0015] The compression deflection coefficient measured in accordance with JIS K6400-2 (2012 edition) E method is 2.8 or less.

[0016] <Method 2>

[0017] (2) A seat cushion made of a polyurethane foam obtained from a composition containing a polyol and an isocyanate, wherein:

[0018] As the polyol, when the total amount of alkylene oxide units is 100 mol %, the polyol contains a polyol having an ethylene oxide unit content of 50 mol % or more,

[0019] The front side and the back side are divided into five equal parts in the thickness direction, and the first layer, the second layer, the third layer, the fourth layer, and the fifth layer are sequentially provided from the front side.

[0020] When the Asker F hardness of the third layer measured from the front side is F3 and the Asker F hardness of the first layer measured from the front side is F1,

[0021] Satisfy F1 / F3<1.0.

[0022] Effects of the Invention

[0023] According to the seat pad of the present disclosure, riding comfort can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a diagram showing a vehicle seat having a seat pad made of polyurethane foam.

[0025] Figure 2 It is a diagram for explaining the first to fifth layers of the seat pad according to the second embodiment.

[0026] Figure 3 This is a plan view of an example of a seat pad according to the first embodiment.

[0027] Figure 4 yes Figure 3 VV line profile. DETAILED DESCRIPTION

[0028] Here, preferred examples of the present disclosure are shown.

[0029] (3) The seat pad according to (2), wherein 0.30≤F1 / F3≤0.70 is satisfied.

[0030] (4) The seat pad according to (2) or (3), wherein the isocyanate contains carbodiimide-modified diphenylmethane diisocyanate.

[0031] (5) The seat pad according to any one of (2) to (4), wherein the compression deflection coefficient measured according to JIS K6400-2 (2012 edition) Method E is 2.8 or less.

[0032] (6) The seat pad according to any one of (2) to (5), wherein the rebound resilience measured in accordance with JIS K6400-3 (2011 edition) is 55% or less.

[0033] (7) The seat pad according to any one of (2) to (6), wherein the stress relaxation rate is 15% or less.

[0034] (8) The seat pad according to any one of (2) to (7), wherein the hysteresis loss rate measured according to JIS K6400-2 (2012 edition) Method E is 20% or less.

[0035] The present disclosure is described in detail below. In addition, in this specification, when "-" is used to describe a numerical range, unless otherwise specified, the lower limit and the upper limit are included. For example, in the description of "10-20", the lower limit "10" and the upper limit "20" are both included. That is, "10-20" has the same meaning as "10 or more and 20 or less".

[0036] 1. Seat pad 110 (first embodiment)

[0037] The seat pad 110 is a seat pad made of polyurethane foam obtained from a composition containing polyol and isocyanate. The compression deflection coefficient of the seat pad 110 measured according to JIS K6400-2 (2012 edition) E method is 2.8 or less.

[0038] (1) Composition

[0039] The seat pad 110 is made of polyurethane foam, preferably flexible polyurethane foam. The polyurethane foam is obtained from a composition containing polyol and isocyanate. The composition may contain at least one selected from a blowing agent, a catalyst, a foam stabilizer and a cross-linking agent as an arbitrary component.

[0040] There is no particular limitation on the polyol. As the polyol, when the total amount of alkylene oxide units is set to 100 mol%, polyol a containing EO units at a content of 50 mol% or more is preferred. For polyol a, the description in the column "Seat pad 10 (second embodiment)" described later is applied as it is, and its description is omitted. For components other than polyol a in the composition, the description in the column "Seat pad 10 (second embodiment)" described later is applied as it is, and its description is omitted.

[0041] (2) Physical properties of the seat pad 110

[0042] (2.1) Compression deflection coefficient

[0043] The compression deflection coefficient was determined as a value obtained by obtaining a force-deflection curve according to JIS K6400-2 (2012 edition) E method and dividing the force at 65% compression by the force at 25% compression.

[0044] Compression deflection coefficient = force at 65% compression / force at 25% compression

[0045] Generally, the smaller the compression flex coefficient, the better the polyurethane foam is considered to be. In addition, the flexural characteristics of the low-load area can be an indicator of the ground contact feeling when a person sits down. The flexural characteristics of the high-load area (for example, more than 700N and less than 980N) can be an indicator of the ground contact feeling when there is vibration such as when driving. The inventors of the present application have obtained the following new insight, namely, in the seat cushion, by making the above-mentioned compression flexural coefficient less than 2.8, it is possible to mainly make the ground contact feeling in the high-load area less likely to be felt. That is, the technology disclosed in the present invention was developed based on the discovery that by reducing the compression flexural coefficient, a seat cushion 110 with good bending and less likely to feel the ground contact can be obtained.

[0046] The compression deflection coefficient of the seat pad 110 (according to JIS K6400-2 (2012 edition) E method) is 2.8 or less, preferably 2.7 or less, and more preferably 2.5 or less. The lower limit of the compression deflection coefficient of the seat pad 110 is not particularly limited, and may be, for example, 2.0 or more, or 2.2 or more.

[0047] The sample used for measurement is the entire seat pad 110 including the surface skin. Figure 3 and Figure 4 In the seat cushion 110 in FIG. 1 , the compression deflection coefficient can be measured as follows. The compression plate 120 is placed on the portion of the seat cushion that contacts the buttocks, and a force-deflection curve is obtained according to JIS K6400-2 (2012 edition) E method. When obtaining the force-deflection curve, the load for returning from compression to decompression when the seat cushion is compressed is set to 980N.

[0048] The force at 65% compression and the force at 25% compression are calculated as follows. The thickness T of the thinnest position P1 located at the bottom of the pressurizing plate 120 is min The initial thickness (thickness before compression) is set to 100%, and the thickness T at the thinnest position P1 is set to min The force when the initial thickness is compressed by 25% to 75% is defined as the force at 25% compression. min The force when the initial thickness is compressed by 65% ​​to 35% of the initial thickness is defined as the force at 65% compression. Then, the compression deflection coefficient is calculated based on the above formula.

[0049] In addition, the shape of the seat cushion is not limited to Figure 3 and Figure 4 For example, the seat pad may be in the shape of a rectangular parallelepiped as in Experimental Examples 1-10 described later. In Experimental Examples 1-6 and 8-10 described later, a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 100 mm including the surface is used as a sample, so the thickness T at the thinnest position P1 is min The initial thickness (thickness before compression) is 100 mm, the thickness at 25% compression is 75 mm, and the thickness at 65% compression is 35 mm. In Experimental Example 7 described later, a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 50 mm including the epidermis is used as the sample, so the thickness T at the thinnest position P1 is min The initial thickness (thickness before compression) is 50 mm, the thickness at 25% compression is 37.5 mm, and the thickness at 65% compression is 17.5 mm.

[0050] (2.2) Hysteresis loss rate

[0051] From the viewpoint of durability, the hysteresis loss rate of the seat pad 110 (according to JIS K6400-2 (2012 edition) E method) is preferably 22% or less, preferably 20% or less, and may be 18% or less, or 15% or less. The lower limit of the hysteresis loss rate is not particularly limited, but is usually 5.0% or more.

[0052] The specimen used for measurement and the method for obtaining the force-deflection curve are the same as (2.1) for the compression deflection coefficient.

[0053] (2.3) Density

[0054] The density of the center portion of the seat pad 110 excluding the front and back surfaces is not particularly limited. From the perspective of weight reduction, the density is preferably 100 kg / m 3 Below, more preferably 80kg / m 3 Below, more preferably 75kg / m 3 The lower limit of the density is not particularly limited, but is usually 20 kg / m 3 From these viewpoints, the density is preferably 20 kg / m 3 Above 100kg / m 3 The following ranges can be obtained by appropriately combining the above lower limits and upper limits.

[0055] In addition, the density of the center portion excluding the front surface and the back surface can be measured as follows.

[0056] Collect a rectangular parallelepiped sample of 100 mm in length, 100 mm in width, and 50 mm in height from the center of the seat cushion 110, excluding the surface. Make the height direction of the sample consistent with the front and back direction of the seat cushion 110. Measure the mass of the collected sample, divide the mass of the sample by the volume, and calculate the density (kg / m 3 ).

[0057] (2.4) 25% hardness

[0058] The 25% hardness (according to JIS K6400-2 (2012 edition) D method) of the seat pad 110 is not particularly limited. The 25% hardness of the entire seat pad 110 is preferably 80N to 400N, more preferably 120N to 300N, and even more preferably 160N to 280N.

[0059] The sample for measuring hardness is set as a rectangular parallelepiped with a length of 400 mm and a width of 400 mm, including the outer and inner skins. For example, in Experimental Examples 1-6, 8-10 described later, a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 100 mm, including the outer skin, is used as the sample. In Experimental Example 7 described later, a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 50 mm, including the outer skin, is used as the sample. A pressure plate with a diameter of 200 mm is used for measurement. During measurement, the sample is placed on the support plate of the testing machine in such a way that the center of the sample is located in the center of the pressure plate.

[0060] (2.5) Stress relaxation rate

[0061] From the viewpoint of durability, the stress relaxation rate of the seat pad 110 is preferably 24% or less, more preferably 20% or less, further preferably 15% or less, and may be 12% or less, 10% or less, 9.0% or less, or 8.0% or less. There is no particular restriction on the lower limit of the stress relaxation rate, and for example, it may be 1.0% or more. The smaller the stress relaxation rate, the less aging of the polyurethane after sitting, and the better the durability. The stress relaxation rate tends to increase as the thickness of the seat pad 110 becomes thinner. The technology disclosed in the present invention is particularly useful in that the stress relaxation rate can be reduced even in a thin seat pad 110.

[0062] In addition, the stress relaxation rate (%) can be measured as follows.

[0063] The sample used for measurement is the entire seat cushion 110 including the surface. The height direction of the sample is made consistent with the front and back direction of the seat cushion 110. Use a circular pressure plate 120 with a diameter of 200 mm to compress the polyurethane foam by a distance of 75% of the initial thickness at a speed of 50 mm / min. Place the pressure plate 120 on the portion of the seat cushion 110 that contacts the buttocks. In the seat cushion 110, the thickness of the position below the center position of the pressure plate 120 is set to the initial thickness (thickness before compression). After that, remove the load and leave it for 1 minute. Apply the load again at the same speed, stop the pressure plate when the load is 196N (20kgf), and read the load after leaving it for 5 minutes. Then, calculate the stress relaxation rate by the following formula.

[0064] Stress relaxation rate (%) = 100 × (load when the pressure plate stops (196N) - load after 5 minutes of standing) / load when the pressure plate stops (196N)

[0065] In addition, the shape of the seat cushion is not limited to Figure 3 and Figure 4 shape. For example, the shape of the seat cushion may be a rectangular parallelepiped as in Experimental Examples 1-10 described later. In Experimental Examples 1-6 and 8-10 described later, since a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 100 mm including the surface is used as a specimen, the thickness of the position below the center position of the pressure plate 120, that is, the initial thickness (thickness before compression) is 100 mm. In Experimental Example 7 described later, since a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 50 mm including the surface is used as a specimen, the thickness of the position below the center position of the pressure plate 120, that is, the initial thickness (thickness before compression) is 50 mm.

[0066] (2.6) Rebound elasticity

[0067] From the viewpoint of improving riding comfort, the rebound elasticity of the seat pad 110 (according to JIS K6400-3 (2011 edition)) is preferably 70% or less, more preferably 60% or less, further preferably 55% or less, and may be 50% or less, 46% or less, or 44% or less. The lower limit of the rebound elasticity of the seat pad 110 is not particularly limited, and may be, for example, 10% or more, 20% or more, or 30% or more.

[0068] 2. Method for manufacturing seat pad 110

[0069] The description in the column “2. Method for manufacturing seat pad 10 ” described later is applied to the seat pad 110 as it is, and the description thereof is omitted.

[0070] 3. Effects of this embodiment

[0071] In recent years, as the thickness of the seat pad 110 of automobiles, ships, airplanes, etc. has become thinner or lighter, ensuring riding comfort has become a problem. Examples of riding comfort include good curvature and a less sense of ground contact.

[0072] The seat pad 110 of this embodiment has a small flexural coefficient, so it is easy to feel the ground contact. For example, according to the seat pad 110 of this embodiment, even if a so-called placement plate is not placed, it is possible to ensure riding comfort, which can contribute to the weight reduction, thickness reduction, and cost reduction of the seat pad 110.

[0073] 4. Seat pad 10 (second embodiment)

[0074] The seat pad 10 is a seat pad made of a polyurethane foam obtained from a composition containing a polyol and an isocyanate. As the polyol, a polyether polyol containing 50 mol% or more of ethylene oxide units is used, when the total amount of alkylene oxide units is 100 mol%. In the seat pad 10, when the front surface 10A and the back surface 10B are divided into five equal parts in the thickness direction, the first layer 11, the second layer 12, the third layer 13, the fourth layer 14, and the fifth layer 15 are sequentially provided from the front surface 10A side, and the Asker F hardness of the third layer 13 measured from the front surface 10A side is F3, and the Asker F hardness of the first layer 11 measured from the front surface 10A side is F1, and F1 / F3<1.0 is satisfied.

[0075] (1) Composition

[0076] The seat cushion 10 is made of polyurethane foam, preferably flexible polyurethane foam. The polyurethane foam is obtained from a composition containing polyol and isocyanate. The composition may contain at least one selected from a blowing agent, a catalyst, a foam stabilizer and a cross-linking agent as an arbitrary component. Each component of the composition is described below.

[0077] (1.1) Polyols

[0078] The polyol is a polyol a containing 50 mol% or more of EO units when the total amount of alkylene oxide units is 100 mol%. Hereinafter, the EO unit content means the content when the total amount of alkylene oxide units is 100 mol%.

[0079] Polyol a is a polyether polyol having a content of EO units of 50 mol % or more. From the viewpoint of reducing stress relaxation rate and hysteresis loss rate, the content of EO units is preferably 60 mol % or more, more preferably 70 mol % or more, further preferably 75 mol % or more, and particularly preferably 80 mol % or more. The upper limit of the content of EO units is not particularly limited and may be 100 mol %. Polyol a may be used in one or more combinations. For example, it may be possible to use a polyol having a content of 75 mol % of EO units and a polyol having a content of 80 mol % of EO units in combination.

[0080] As other alkylene oxides other than ethylene oxide used for the manufacture of polyol a, propylene oxide, butylene oxide, etc. can be mentioned. As other alkylene oxides other than ethylene oxide, propylene oxide is suitable. As polyol a, a polyol in which all propylene oxide units (hereinafter referred to as "PO units") except EO units can be appropriately used.

[0081] The number average molecular weight of polyol a is not particularly limited. From the viewpoint of achieving low rebound resilience, the number average molecular weight of polyol a is preferably 20,000 or less, more preferably 15,000 or less, further preferably 10,000 or less, more preferably 7,000 or less, and more preferably 5,000 or less. The lower limit of the number average molecular weight of polyol a is usually 2,000 or more, and may also be 1,000 or more.

[0082] The number average molecular weight of polyol a can be measured by gel permeation chromatography (GPC). In the case where polyol a is a commercially available product, the catalog value can be used as the number average molecular weight of polyol a.

[0083] The number of functional groups of polyol a is not particularly limited. From the viewpoint of reducing the stress relaxation rate and the hysteresis loss rate, the number of functional groups of polyol a is preferably less than 3, more preferably less than 2.5, and further preferably 2. The number of functional groups of polyol a is usually more than 2. As polyol a, a polyoxyethylene / propylene glycol copolymer having an EO unit content of 50 mol% or more is preferred.

[0084] If the number of functional groups of polyol a is the above value, the formation of a network structure can be suppressed when the polyol reacts with isocyanate. It is speculated that the entanglement of polyurethane molecules during compression of the polyurethane foam thus formed is suppressed, and the stress relaxation rate and hysteresis loss rate are reduced.

[0085] In addition, in the present disclosure, the number of functional groups refers to the average value of the number of active hydrogen groups possessed by each component contained in the polyol. When the polyol is a commercially available product, the catalog value can be used as the number of functional groups of the polyol a.

[0086] The content of polyol a is not particularly limited. The content of polyol a is greater than 0 mass parts, preferably 20 mass parts or more, more preferably 40 mass parts or more, and can also be 50 mass parts or more, 60 mass parts or more, 70 mass parts or more, 80 mass parts or more. From the viewpoint of formability, the upper limit of the content of the above-mentioned polyol a is preferably 95 mass parts or less, more preferably 93 mass parts or less, and further preferably 90 mass parts or less. From these viewpoints, the content of polyol a is preferably 20 mass parts or more and 95 mass parts or less, and can be the range of the above-mentioned lower limit and upper limit appropriately combined.

[0087] The polyol may contain other polyols other than polyol a (hereinafter, also referred to as "other polyols"). As long as the other polyols are polyols having an ethylene oxide unit content of less than 50 mol% (which may not contain ethylene oxide units), there is no particular restriction. As other polyols, for example, polyether polyols having an ethylene oxide unit content of less than 50 mol%, polymer polyols having an ethylene oxide unit content of less than 50 mol%, polyester polyols, etc. can be used. From the viewpoint of various physical properties such as impact absorbency, other polyols are preferably polyether polyols having an ethylene oxide unit content of less than 50 mol%. Other polyols may be used alone or in combination of two or more.

[0088] The number of functional groups of other polyols is not particularly limited. The number of functional groups of other polyols is preferably less than 3, more preferably 2.5 or less, and further preferably 2. The number of functional groups of other polyols is usually 2 or more.

[0089] If the number of functional groups of the other polyols is the above value, the formation of a network structure can be suppressed when the polyols react with isocyanate. It is speculated that the entanglement of polyurethane molecules during compression of the polyurethane foam thus formed is suppressed, and the stress relaxation rate and hysteresis loss rate are reduced.

[0090] The number average molecular weight of other polyols is not particularly limited. The number average molecular weight of the polyol is preferably 2,000 to 20,000, more preferably 2,500 to 15,000, and more preferably 3,000 to 10,000.

[0091] As other polyols, for example, polyether polyols containing PO units, butylene oxide units, etc. as other alkylene oxide units other than EO units can be cited. Hereinafter, the polyether polyol is referred to as polyol b. As polyol b, preferably, polyoxyethylene / propylene glycol copolymers, polypropylene glycol (PPG), polytetramethylene ether glycol (PTMG) having an EO unit content of less than 50 mol%, more preferably polyoxyethylene / propylene glycol copolymers having an EO unit content of less than 50 mol%. As other polyols, polyols other than polyol b can be used within the range of properties such as the rebound elasticity, stress relaxation rate, and hysteresis loss rate of the polyurethane foam. Polyols other than polyol b can be used only one, or two or more can be used in combination.

[0092] The content of the EO unit of the polyol b is not particularly limited. For example, from the viewpoint of reducing the stress relaxation rate and the hysteresis loss rate, the content of the EO unit of the polyol b is preferably greater than 0 mol%, more preferably 10 mol% or more, and further preferably 15 mol% or more. The upper limit of the content of the EO unit of the polyol b is not particularly limited, and it only needs to be less than 50 mol%.

[0093] The content of polyol b is not particularly limited. From the viewpoint of improving buffering, when the total amount of polyol is set to 100 parts by mass, the content of polyol b is preferably 5 parts by mass or more, more preferably 8 parts by mass or more, and further preferably 12 parts by mass or more. From the viewpoint of making the amount of polyol a sufficient to ensure the softness of the surface, the content of the above-mentioned polyol b is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and particularly preferably 30 parts by mass or less. From these viewpoints, the content of polyol b is preferably 5 parts by mass or more and 50 parts by mass or less, more preferably 8 parts by mass or more and 40 parts by mass or less, and further preferably 12 parts by mass or more and 30 parts by mass or less.

[0094] When polyol a and polyol b are used in combination, the cushioning properties of the polyurethane foam can be improved. The reason for this is not clear, but it is presumed as follows.

[0095] When only polyol a is used as the polyol, a coarse foam with low cushioning property can be obtained. When only polyol a is used as the polyol, the components of the polyol are homogenized and the reaction proceeds rapidly, which is considered to be one of the reasons for the decrease in cushioning property. It can be inferred that by using polyol a and polyol b, which is a polyether polyol with different properties from polyol a, as the polyol, the reaction can be slowed down and the cushioning property can be improved.

[0096] (1.2) Foaming agent

[0097] The foaming agent is an arbitrary component. The foaming agent can be water, alternative fluorochlorocarbons or hydrocarbons such as n-pentane, etc., alone or in combination. As the foaming agent, water is particularly preferred. In the case of water, carbon dioxide gas is generated when the polyol reacts with the isocyanate, and foaming is performed by the carbon dioxide gas. The amount of water as the foaming agent is preferably 1.0 mass parts to 4.0 mass parts relative to 100 mass parts of the polyol, more preferably 1.5 mass parts to 3.5 mass parts, and further preferably 2.0 mass parts to 3.0 mass parts.

[0098] (1.3) Catalyst

[0099] The catalyst is an optional component. A known catalyst for polyurethane foam can be used as the catalyst. Examples of the catalyst include resinification catalysts and foaming catalysts. The resinification catalyst is a catalyst that promotes the urethane reaction (resinification reaction) of polyols and isocyanates. The resin-forming catalyst is not limited, and examples thereof include amine catalysts such as triethylenediamine, 1,2-dimethylimidazole, N·(N',N'-dimethylaminoethyl)-morpholine, tetramethylguanidine, dimethylethanolamine, N-methyl-N'-(2-hydroxyethyl)-piperazine, N,N,N',N'-tetramethylpropane 1,3-diamine, N,N'-dimethylpiperazine, N,N,N',N'-tetramethylhexane-1,6-diamine, N,N,N',N",N"pentamethyldipropylene-triamine, N-(2-hydroxyethyl)morpholine, ethylene glycol bis(3-dimethyl)-aminopropyl ether, N,N-dimethylcyclohexylamine, and N-methyl-N'-(2-dimethylamino)ethylpiperazine. The foaming catalyst is a catalyst that promotes the reaction of isocyanate and water to generate carbon dioxide gas. The foaming catalyst is not limited, and examples thereof include amine catalysts such as bis(2-dimethylaminoethyl) ether, triethylamine, dimethylaminoethoxyethanol, N,N,N'-trimethylaminoethyl-ethanolamine, and N,N,N',N",N"-pentamethyldiethylenetriamine.

[0100] The total amount of the catalyst is preferably 0.2 parts by mass or more and 3.0 parts by mass or less relative to 100 parts by mass of the polyol.

[0101] (1.4) Foam stabilizer

[0102] The foam stabilizer is an optional component. The foam stabilizer may be any foam stabilizer generally used as a raw material for polyurethane foam, and examples thereof include silicone compounds and nonionic surfactants. The amount of the foam stabilizer is preferably 0.05 parts by mass or more and 2.0 parts by mass or less relative to 100 parts by mass of the polyol.

[0103] (1.5) Cross-linking agent

[0104] The crosslinking agent is an optional component. The crosslinking agent is added to increase the hardness and tear strength of the polyurethane foam, and is particularly effective in increasing the hardness.

[0105] As the crosslinking agent, polyols such as trimethylolpropane, glycerol, 1,4-butanediol, diethylene glycol, or amines such as ethanolamines and polyethylene polyamines can be cited. Two or more crosslinking agents can be used. The total amount of the crosslinking agent is preferably 0.1 to 6.0 parts by mass relative to 100 parts by mass of the polyol.

[0106] (1.6) Isocyanate

[0107] There is no particular limitation on the isocyanate. As the isocyanate, MDI-based isocyanate (diphenylmethane diisocyanate-based isocyanate) is preferred. When MDI-based isocyanate is used, for example, compared with the case of using TDI (toluene diisocyanate), the front surface 10A of the polyurethane foam can have a soft touch.

[0108] As MDI type isocyanates, specifically, pure MDI such as 2,2'-diphenylmethane diisocyanate (2,2'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), and 4,4'-diphenylmethane diisocyanate (4,4'-MDI) can be cited; a mixture of diphenylmethane diisocyanate and polymethylene polyphenyl polyisocyanate, i.e., polymeric MDI; their carbodiimide modified bodies, urethane modified bodies, urea modified bodies, allophanate modified bodies, biuret modified bodies, isocyanurate modified bodies, etc.; and MDI prepolymers obtained by reacting these isocyanates with polyols, etc. MDI type isocyanates can also be used in combination of multiple types.

[0109] Among them, the isocyanate preferably contains carbodiimide-modified diphenylmethane diisocyanate, more preferably contains pure MDI and carbodiimide-modified diphenylmethane diisocyanate, and more preferably is a mixture of pure MDI, carbodiimide-modified diphenylmethane diisocyanate and polymerized MDI. From the viewpoint of inhibiting the formation of a mesh structure when the polyol reacts with the isocyanate, when the total amount of the isocyanate is set to 100 parts by mass, the total amount of pure MDI and carbodiimide-modified diphenylmethane diisocyanate is preferably 60 parts by mass or more, more preferably 70 parts by mass or more, and more preferably 80 parts by mass or more. The upper limit of the total amount of pure MDI and carbodiimide-modified diphenylmethane diisocyanate is not particularly limited and can be 100 parts by mass. The mass ratio of the total amount of pure MDI and carbodiimide-modified diphenylmethane diisocyanate to the amount of polymeric MDI is preferably 60:40-100:0, more preferably 70:30-98:2, and more preferably 80:20-96:4.

[0110] The isocyanate index (INDEX) is preferably 80 or more, preferably 90 or more, more preferably 97 or more, and particularly preferably 100 or more. The isocyanate index is preferably 120 or less, more preferably 110 or less. The isocyanate index can be, for example, a range combining the upper limit and the lower limit described above, for example, 97 or more and 120 or less.

[0111] The isocyanate index is a value obtained by dividing the number of moles of isocyanate groups in isocyanate by the total number of moles of active hydrogen groups such as hydroxyl groups of polyol or water as a blowing agent and multiplying the result by 100, and is calculated as (NCO equivalent of isocyanate / active hydrogen equivalent×100).

[0112] (1.7) Other ingredients

[0113] Examples of other additives that may be appropriately blended include flame retardants and colorants.

[0114] The flame retardant is added to make the polyurethane foam less flammable. As the flame retardant, known liquid flame retardants or solid flame retardants can be cited. For example, organic flame retardants such as polyvinyl chloride, chloroprene rubber, chlorinated polyethylene, phosphate esters or halogenated phosphate compounds, or melamine resins or urea resins, inorganic flame retardants such as antimony oxide or aluminum hydroxide can be cited. The flame retardant is not limited to one, and two or more can also be used in combination. The total amount of the flame retardant is preferably 0.1 mass parts or more and 6.0 mass parts or less relative to 100 mass parts of the polyol.

[0115] The colorant is blended to give the polyurethane foam an appropriate color, and a colorant corresponding to a desired color is used. Examples of the colorant include pigments, graphite, and the like.

[0116] (2) Physical properties of the seat pad 10

[0117] In the present disclosure, the surface on the seat occupant's side when the seat occupant is seated on the seat cushion 10 is defined as the front surface 10A of the seat cushion 10, and the surface on the opposite side to the front surface 10A is defined as the back surface 10B of the seat cushion 10. The front surface 10A of the seat cushion 10 can be appropriately formed into a surface that contacts the bottom surface of the lower mold when the seat cushion 10 is formed using a molding mold, for example. The front surface 10A of the seat cushion 10 is usually oriented upward when the seat cushion 10 is installed in a vehicle. Figure 1 In FIG. 1 , the upper side is indicated by an arrow UP, and the lower side is indicated by an arrow DW.

[0118] The size and shape of the seat cushion 10 are not particularly limited as long as it can support the buttocks of the seated person (e.g., buttocks, back, waist). The thickness of the portion of the seat cushion 10 that supports the buttocks of the seated person is, for example, 20 mm or more, 30 mm or more, preferably 40 mm or more, more preferably 50 mm or more, and even more preferably 60 mm or more. The thickness of the above-mentioned portion of the seat cushion 10 is usually 120 mm or less, and can be, for example, 100 mm or less, 80 mm or less, 75 mm or less, or 70 mm or less.

[0119] The properties related to the softness of the surface of the seat pad 10 described below are the results of measurement of a test piece, but the same properties are also shown in a product shape.

[0120] (2.1) Asker F hardness (surface softness)

[0121] like Figure 2 As shown, in the case of the seat pad 10, when the space between the front surface 10A and the back surface 10B is divided into five equal parts in the thickness direction, and the first layer 11, the second layer 12, the third layer 13, the fourth layer 14, and the fifth layer 15 are provided in order from the front surface 10A side, the Asker F hardness of the third layer 13 measured from the front surface 10A side is F3, and the Asker F hardness of the first layer 11 measured from the front surface 10A side is F1, the following formula (1) is satisfied. From the viewpoint of ensuring the softness of the surface and maintaining the posture of the seated person, the seat pad 10 preferably satisfies any one of the following formulas (2) to (4).

[0122] F1 / F3<1.0……(1)

[0123] F1 / F3≤0.85……(2)

[0124] F1 / F3≤0.70……(3)

[0125] F1 / F3≤0.65……(4)

[0126] Furthermore, the seat pad 10 may satisfy any one of the following formulas (5) to (7), for example.

[0127] 0.20≤F1 / F3……(5)

[0128] 0.30≤F1 / F3……(6)

[0129] 0.40≤F1 / F3……(7)

[0130] From these viewpoints, the seat pad 10 preferably satisfies 0.20≤F1 / F3≤0.85, more preferably satisfies 0.30≤F1 / F3≤0.70, and further preferably satisfies 0.40≤F1 / F3≤0.65.

[0131] In addition, the Asker F hardness is measured using an Asker durometer F type, and the Asker durometer F type is set on the sample, and the value after 20 seconds is read. The sample for measuring the Asker F hardness is a square plate with a length and a width of 400 mm respectively. The thickness of the sample is the thickness of the seat pad 10 divided into five equal parts in the thickness direction mentioned above. The Asker F hardness F1 is measured by setting an Asker durometer F type at the center of the front surface 10A of the first layer 11. The Asker F hardness F3 is measured by setting an Asker durometer F type at the center of the surface on the front surface 10A side of the third layer 13. In addition, in the description described later, the Asker F hardness of the second layer 12 measured from the front surface 10A side is set to F2, and the Asker F hardness of the fourth layer 14 measured from the front surface 10A side is set to F4. The Asker F hardness F2 is measured by setting an Asker durometer F type at the center of the surface on the front surface 10A side of the second layer 12. The Asker F hardness F4 is measured by setting an Asker hardness type F at the center of the surface on the front surface 10A side of the fourth layer 14. The Asker F hardness measured from the back surface 10B side of the fifth layer 15 is set to F5. The Asker F hardness F5 is measured by setting an Asker hardness type F at the center of the back surface 10B of the fifth layer 15.

[0132] The Asker F hardness of each layer of the seat pad 10 is not particularly limited as long as it satisfies the above-mentioned requirements. The Asker F hardness of each layer of the seat pad 10 may further satisfy one or more of the following requirements.

[0133] From the viewpoint of ensuring the softness of the surface and appropriately maintaining the posture of the seated person, the seat pad 10 preferably satisfies F1 / F2<1.0. According to this structure, sufficient hardness can be ensured at a portion of the seat pad 10 that is 1 / 5 or more of the thickness away from the surface, and the seat pad 10 can be appropriately realized in which the surface layer portion that is less than 20% of the entire thickness is soft. Furthermore, the seat pad 10 can satisfy any one of the formulas (8) to (10).

[0134] 0.30≤F1 / F2≤0.85……(8)

[0135] 0.30≤F1 / F2≤0.70……(9)

[0136] 0.40≤F1 / F2≤0.65……(10)

[0137] The seat pad 10 may satisfy any one of the following formulas (11) to (13) from the viewpoint of ensuring the softness of the surface and ensuring the hardness of the back surface 10B side of the seat pad 10. When any one of the formulas (11) to (13) is satisfied, for example, even without placing a separate polyurethane foam (so-called placement plate) having a higher hardness than the front surface 10A side on the back surface 10B side, the posture of the seated person can be appropriately maintained.

[0138] 0.55≤F1 / F5≤0.90……(11)

[0139] 0.60≤F1 / F5≤0.85……(12)

[0140] 0.65≤F1 / F5≤0.80……(13)

[0141] More specifically, the seat pad 10 may be made of polyurethane foam. When a regular quadrangular prism-shaped sample having a length of 400 mm, a width of 400 mm, and a thickness of 100 mm is prepared and the Asker F hardness of each layer is measured, the following hardness is shown.

[0142] From the viewpoint of surface softness, the Asker F hardness F1 is preferably 60 or less, more preferably 50 or less, and further preferably 40 or less. From the viewpoint of ease of manufacturing, the Asker F hardness F1 is preferably 12 or more, more preferably 15 or more, and further preferably 20 or more. From these viewpoints, the Asker F hardness F1 is preferably 12 or more and 60 or less, more preferably 15 or more and 50 or less, and further preferably 20 or more and 40 or less.

[0143] From the viewpoint of maintaining the posture of the seated person, the Asker F hardness F3 is preferably 18 or more, more preferably 20 or more, and further preferably 30 or more. From the viewpoint of ease of manufacturing, the Asker F hardness F3 is preferably 80 or less, more preferably 75 or less, and further preferably 70 or less. From these viewpoints, the Asker F hardness F3 is preferably 18 or more and 80 or less, more preferably 20 or more and 75 or less, and further preferably 30 or more and 70 or less.

[0144] From the viewpoint of the softness of the surface and the maintenance of the seated person's posture, the absolute value of the difference between F1 and F3 (|F3-F1|) is preferably 4 or more, and may be 10 or more, 15 or more, 20 or more, or 25 or more. The upper limit of the absolute value of the difference between F1 and F3 is not particularly limited, and may be, for example, 50 or less, 45 or less, or 40 or less.

[0145] From the viewpoint of maintaining the posture of the seated person and ease of manufacturing, the Asker F hardness F2 is preferably 18 to 80, more preferably 20 to 75, and even more preferably 30 to 70.

[0146] From the viewpoint of ensuring the hardness of the back surface 10B side of the seat pad 10 and ease of manufacturing, the Asker F hardness F4 is preferably 18 to 80, more preferably 20 to 75, and even more preferably 30 to 70.

[0147] From the viewpoint of ensuring the hardness of the back surface 10B side of the seat pad 10 and ease of manufacturing, the Asker F hardness F5 is preferably 15 to 65, more preferably 18 to 60, and even more preferably 25 to 55.

[0148] From the viewpoint of maintaining the seated person's posture, the absolute value of the difference between F2 and F3 (|F3-F2|) is preferably 6 or less, and more preferably 5 or less. The lower limit of the absolute value of the difference between F2 and F3 is 0.

[0149] From the viewpoint of maintaining the seated person's posture, the absolute value of the difference between F4 and F3 (|F3-F4|) is preferably 5 or less, and more preferably 4 or less. The lower limit of the absolute value of the difference between F4 and F3 is 0.

[0150] The Asker F hardness of each layer of the seat pad 10 can be controlled by adjusting the types of components contained in the composition of the polyurethane foam, the mixing ratio of each component, etc. For example, if the amount of the foaming agent added is increased, the Asker F hardness F1 of the first layer 11 can be maintained, and the Asker F hardness F3 of the third layer 13 can be increased. For example, if the amount of the cross-linking agent added is reduced, the Asker F hardness F1 of the first layer 11 can be maintained, and the Asker F hardness F3 of the third layer 13 can be increased. In addition, if the isocyanate index is increased, there is a tendency for F1 / F3 to become smaller. Furthermore, in the case where the seat pad 10 is a mold foam, by appropriately setting the orientation of the molding mold relative to the vertical direction, the reactivity during molding can be adjusted to control the Asker F hardness of each layer.

[0151] The hardness of each layer of the seat pad 10 may be measured using a hardness measurement method other than the above-mentioned hardness measurement method, such as 25% hardness (based on JIS K6400-2 (2012 edition) D method), and the same characteristics are also shown.

[0152] (2.2) Density

[0153] The density of the center portion of the seat pad 10 excluding the front surface 10A and the back surface 10B is not particularly limited. From the viewpoint of weight reduction, the density is preferably 100 kg / m3 Below, more preferably 80kg / m 3 Below, more preferably 75kg / m 3 The lower limit of the density is not particularly limited, but is usually 20 kg / m 3 From these viewpoints, the density is preferably 20 kg / m 3 Above 100kg / m 3 The following ranges can be obtained by appropriately combining the above lower limits and upper limits.

[0154] In addition, the density of the central portion excluding the front surface 10A and the back surface 10B can be measured as follows.

[0155] Collect a rectangular parallelepiped sample of 100 mm in length, 100 mm in width, and 50 mm in height from the center of the seat cushion 10, excluding the surface. Make the height direction of the sample consistent with the front and back direction of the seat cushion 10. Measure the mass of the collected sample, divide the mass of the sample by the volume, and calculate the density (kg / m 3 ).

[0156] (2.3) 25% hardness

[0157] The 25% hardness (according to JIS K6400-2 (2012 edition) D method) of the seat pad 10 is not particularly limited. The 25% hardness of the entire seat pad 10 is preferably 80N to 400N, more preferably 120N to 300N, and even more preferably 160N to 280N.

[0158] The sample for measuring the hardness is set as a rectangular parallelepiped with a length of 400 mm and a width of 400 mm, including the skin of the front and back. For example, in Experimental Examples 1-6, 8-10 described later, a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 100 mm, including the skin, is used as the sample. In Experimental Example 7 described later, a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 50 mm, including the skin, is used as the sample. A pressure plate with a diameter of 200 mm is used for measurement. During measurement, the sample is placed on the support plate of the testing machine in such a way that the center of the sample is located in the center of the pressure plate.

[0159] (2.4) Hysteresis loss rate

[0160] From the viewpoint of durability, the hysteresis loss rate of the seat pad 10 (according to JIS K6400-2 (2012 edition) E method) is preferably 22% or less, preferably 20% or less, and may be 18% or less, or 15% or less. The lower limit of the hysteresis loss rate is not particularly limited, but is usually 5.0% or more. In addition, when obtaining a force-deflection curve according to JIS K6400-2 (2012 edition) E method, the load for returning from pressurization to decompression when the seat pad is compressed is set to 980N.

[0161] The sample for measurement is obtained as follows. The entire seat pad 10 including the surface is used as the sample. For example, in Experimental Examples 1-6, 8-10 described later, a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 100 mm including the surface is used as the sample. In Experimental Example 7 described later, a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 50 mm including the surface is used as the sample. The height direction of the sample is made consistent with the front and back direction of the seat pad 10.

[0162] (2.5) Compression deflection coefficient

[0163] From the viewpoint of reducing the ground feel, the compression deflection coefficient (according to JIS K6400-2 (2012 edition) E method) of the seat pad 10 is preferably 2.9 or less, and may be 2.7 or less, or 2.5 or less. The lower limit of the compression deflection coefficient of the seat pad 10 is not particularly limited, and may be, for example, 2.0 or more, or 2.2 or more.

[0164] The method for obtaining the specimen and force-deflection curve used for measurement is the same as the method for obtaining the specimen and force-deflection curve used for measurement of hysteresis loss rate (2.4).

[0165] (2.6) Stress relaxation rate

[0166] From the viewpoint of durability, the stress relaxation rate of the seat pad 10 is preferably 24% or less, more preferably 20% or less, further preferably 15% or less, and may be 12% or less, 10% or less, 9.0% or less, or 8.0% or less. There is no particular restriction on the lower limit of the stress relaxation rate, and for example, it may be 1.0% or more. The smaller the stress relaxation rate, the less aging of the polyurethane after sitting down, and the better the durability. The stress relaxation rate tends to increase as the thickness of the seat pad 10 decreases. The technology disclosed in the present invention is particularly useful in that the stress relaxation rate can be reduced even in a thin seat pad 10.

[0167] In addition, the stress relaxation rate (%) can be measured as follows.

[0168] The entire seat pad 10 including the surface is used as a sample. For example, in Experimental Examples 1-6, 8-10 described later, a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 100 mm including the surface is used as a sample. In Experimental Example 7 described later, a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 50 mm including the surface is used as a sample. The height direction of the sample is made consistent with the front and back direction of the seat pad 10. Using a circular pressure plate with a diameter of 200 mm, compress the polyurethane foam at a speed of 50 mm / min for a distance of 75% of the initial thickness. After that, remove the load and leave it for 1 minute. Apply the load again at the same speed, stop the pressure plate when the load is 196N (20kgf), and read the load after leaving it for 5 minutes. Then, calculate the stress relaxation rate by the following formula.

[0169] Stress relaxation rate (%) = 100 × (load when the pressure plate stops (196N) - load after 5 minutes of standing) / load when the pressure plate stops (196N)

[0170] (2.7) Rebound elasticity

[0171] From the viewpoint of improving riding comfort, the rebound elasticity of the seat pad 10 (according to JIS K6400-3 (2011 edition)) is preferably 70% or less, more preferably 60% or less, further preferably 55% or less, and may be 50% or less, 46% or less, or 44% or less. The lower limit of the rebound elasticity of the seat pad 10 is not particularly limited, and may be, for example, 10% or more, 20% or more, or 30% or more.

[0172] 5. Method for manufacturing seat pad 10

[0173] The seat pad 10 can be manufactured by a known foaming method in which a composition is stirred and mixed to react a polyol with an isocyanate. The foaming method includes slab foaming and mold foaming, and any molding method may be used. The seat pad 10 is preferably a mold foam. Mold foaming is a method in which a mixed composition is filled into a mold (molding mold) and foamed in the mold. In the case where the seat pad 10 is a mold foam, from the viewpoint of the softness of the surface, the front side 10A is the surface in contact with the lower surface of the molding space, and the back side 10B is the surface in contact with the upper surface of the molding space.

[0174] 6. Effects of this embodiment

[0175] In recent years, as the thickness of seat pads 10 of automobiles, ships, airplanes, etc. has become thinner and lighter, ensuring riding comfort has become a problem. Riding comfort includes the softness of the surface of the seat that makes the seat feel good when sitting, and the durability for maintaining the posture of the seated person.

[0176] The seat pad 10 of this embodiment has excellent surface softness, so it can achieve a good touch. In addition, the seat pad 10 of this embodiment can ensure the hardness of the center part in the thickness direction, so it has excellent durability for maintaining the posture of the seated person. For example, according to the seat pad 10 of this embodiment, even if the so-called placement plate is not placed, it is possible to ensure riding comfort, which can contribute to the weight reduction, thickness reduction, and cost reduction of the seat pad 10.

[0177] In addition, according to the present embodiment, the hysteresis loss rate and the stress relaxation rate can be reduced, and the seat pad 10 with high durability can be realized without being easily deteriorated (see Figure 1 ).

[0178] Example

[0179] Hereinafter, the present disclosure will be specifically described by way of examples. In Tables 1 and 2, when a “*” is marked, such as “Experimental Example 1*”, it indicates a comparative example. Experimental Examples 3 to 10 are examples, and Experimental Examples 1 and 2 are comparative examples.

[0180] 1. Sample preparation

[0181] The composition prepared according to the ratio in Table 1 was foamed by a mold to produce the samples of each experimental example. The samples of Experimental Examples 1-6 and 8-10 were in the shape of a regular quadrangular prism with a length of 400 mm, a width of 400 mm, and a thickness of 100 mm. The sample of Experimental Example 7 was in the shape of a regular quadrangular prism with a length of 400 mm, a width of 400 mm, and a thickness of 50 mm.

[0182] Details of the main raw materials are as follows.

[0183] Polyol a: Polyoxyethylene / propylene glycol copolymer, EO unit content 80 mol%, PO unit content 20 mol%, number average molecular weight 4000, number of functional groups 2, hydroxyl value 28 mg / KOHg

[0184] Polyol b: Polyoxyethylene / propylene glycol copolymer, EO unit content 20 mol%, PO unit content 80 mol%, number average molecular weight 4000, number of functional groups 2, hydroxyl value 28 mg / KOHg

[0185] Polyol c: polyether polyol, EO unit content 15 mol%, number average molecular weight 7000, number of functional groups 3, hydroxyl value 24 mg / KOHg

[0186] Polyol d: polymer polyol, EO unit content 15 mol%, number average molecular weight 5000, number of functional groups 3, hydroxyl value 24 mg / KOHg

[0187] Polyol e: polyether polyol, EO unit content 15 mol%, number average molecular weight 5000, number of functional groups 3, hydroxyl value 34 mg / KOHg

[0188] Foaming agent: water

[0189] Catalyst 1: Resinizing catalyst, triethylenediamine 33%

[0190] Catalyst 2: Foaming catalyst, bis(2-dimethylaminoethyl) ether

[0191] Foam stabilizer 1: Silicone foam stabilizer, product number: L-3184J, manufactured by MOMENTIVE

[0192] Foam stabilizer 2: Silicone foam stabilizer, product number: B8715LF2, manufactured by EVONIK

[0193] Foam stabilizer 3: Silicone foam stabilizer, product number: B8738LF2, manufactured by Evonik

[0194] Crosslinker 1: Trimethylolpropane trimethacrylate

[0195] Cross-linking agent 2: glycerol

[0196] Cross-linking agent 3: N,N-diethanolamine 80%

[0197] Isocyanate 1: A mixture of pure MDI (4,4'-MDI) and carbodiimide-modified diphenylmethane diisocyanate (95%) and polymeric MDI (5%)

[0198] Isocyanate 2: a mixture of 80% toluene diisocyanate (TDI) and 20% polymeric MDI [Table 1]

[0199]

[0200] [Table 2]

[0201]

[0202] 2. Evaluation Method 1

[0203] Samples were cut out from the polyurethane foam produced using the above raw materials, and the hysteresis loss rate, stress relaxation rate, rebound elasticity, etc. were measured by the following methods. The results are recorded in Table 1 and Table 2. In Experimental Example 2, since demolding was not possible, physical properties were not evaluated.

[0204] (1) Density

[0205] Density (kg / m 3) is measured using the method described in the implementation method.

[0206] (2) 25% hardness

[0207] The 25% hardness (N) was measured by the method described in the embodiment. That is, the 25% hardness was measured by the method described in the embodiment. That is, in Experimental Examples 1-6, 8-10, a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 100 mm including the epidermis was used as a sample. In Experimental Example 7, a rectangular parallelepiped with a length of 400 mm, a width of 400 mm, and a height of 50 mm including the epidermis was used as a sample.

[0208] (3) Hysteresis loss rate

[0209] The hysteresis loss rate (%) is measured according to JIS K6400-2E method. The smaller the value, the better the posture stability (durability) when sitting.

[0210] (4) Compression deflection coefficient

[0211] The compression deflection coefficient (%) is measured according to JIS K6400-2E method. The smaller the value, the better the vibration absorption.

[0212] (5) Stress relaxation rate

[0213] The stress relaxation rate (%) is measured by the method described in the embodiment. The smaller the value, the better the posture stability (durability) when sitting.

[0214] (6) Rebound elasticity

[0215] The rebound elasticity (%) is measured in accordance with JIS K6400-3 (2011 edition). By appropriately suppressing the rebound elasticity, riding comfort can be improved.

[0216] 3. Evaluation Method 2

[0217] The Asker F hardness of each layer of the sample prepared using the above raw materials was measured by the method described in the embodiment, and the ratio of the Asker F hardness of the first layer to the Asker F hardness of each layer was calculated. The results are recorded in Table 1 and Table 2.

[0218] (1) Asker F hardness

[0219] The Asker F hardness of each layer from the first layer to the fifth layer was measured by the method described in the embodiment.

[0220] (2) Ratio of the Asker F hardness of the first layer to the Asker F hardness of each layer

[0221] The ratio of the Asker F hardness of the first layer to the Asker F hardness of each layer is calculated by dividing the Asker F hardness of the first layer by the Asker F hardness of each layer. In Tables 1 and 2, for example, the ratio of the Asker F hardness of the first layer to the Asker F hardness of the third layer is shown in "First layer / third layer".

[0222] 4. Result 1

[0223] Experimental Example 3-10 satisfies the following requirements ac.

[0224] Requirement a: The seat pad is made of a polyurethane foam obtained from a composition containing a polyol and an isocyanate.

[0225] Requirement b: A polyol containing 50 mol% or more of ethylene oxide units when the total amount of alkylene oxide units is 100 mol%.

[0226] Requirement c: F1 / F3<1.

[0227] In addition, Experimental Example 1 does not satisfy requirements b and c. Experimental Example 2 does not satisfy requirement a. Experimental Example 3-10 satisfying requirements ac has better surface softness and durability than Comparative Example 1. Experimental Example 3-10 satisfying requirements ac shows the characteristics of the first layer (F1) < fifth layer (F5) < third layer (F3).

[0228] In addition, among Experimental Examples 3 to 10, Experimental Example 4 to 10 further satisfied the following requirement d. Experimental Example 4 to 10 further satisfied the requirement d, and the surface flexibility of Experimental Example 4 to 10 was further improved.

[0229] Requirement d: 0.30≤F1 / F3≤0.70.

[0230] In addition, Experimental Example 3-10 further satisfied the following requirement e. Experimental Example 3-10 further satisfying the requirement e could appropriately obtain a polyurethane foam having excellent surface softness and durability.

[0231] Requirement e: The isocyanate contains carbodiimide-modified diphenylmethane diisocyanate.

[0232] In addition, Experimental Example 3-10 further satisfied the following requirement f. Experimental Example 3-10 further satisfying the requirement f had good vibration absorption.

[0233] Requirement f: The compression deflection coefficient measured in accordance with JIS K6400-2 (2012 edition) Method E is 2.8 or less.

[0234] In addition, among the experimental examples 3 to 10, the experimental example 4 to 10 further satisfied the following requirement g. The experimental example 4 to 10 further satisfying the requirement g was excellent in riding comfort.

[0235] Requirement g: The rebound elasticity measured in accordance with JIS K6400-3 (2011 edition) is 55% or less.

[0236] In addition, among Experimental Examples 3-10, Experimental Examples 3-8 and 10 further satisfied the following requirement h. Experimental Examples 3-8 and 10 further satisfying the requirement h had good durability.

[0237] Requirement h: The stress relaxation rate is 15% or less.

[0238] In addition, among Experimental Examples 3 to 10, Experimental Examples 4-7 and 10 further satisfied the following requirement i. Experimental Examples 4-7 and 10 further satisfying the requirement i had good durability.

[0239] Requirement i: The hysteresis loss rate measured in accordance with JIS K6400-2 (2012 edition) Method E is 20% or less.

[0240] Experimental Example 5 was compared with Experimental Example 4 in which the amount of foaming agent added was less than that of Experimental Example 5. The Asker F hardness of the first layer of Experimental Example 5 and Experimental Example 4 was approximately the same. The first layer / third layer (F1 / F3) of Experimental Example 5 was smaller than that of Experimental Example 4. This result suggests that the softness and durability of the surface can be improved by increasing the amount of foaming agent added. In addition, it is suggested that the technology disclosed in the present invention is effective even when the density of the seat pad is reduced.

[0241] Experimental Example 5 was compared with Experimental Example 6 in which the amount of crosslinking agent added was greater than that of Experimental Example 5. The Asker F hardness of the first layer of Experimental Example 5 and Experimental Example 6 was approximately the same. The first layer / third layer (F1 / F3) of Experimental Example 5 was smaller than that of Experimental Example 6. This result suggests that the softness and durability of the surface can be improved by reducing the amount of additives.

[0242] Experimental Example 5 with a thickness of 100 mm was compared with Experimental Example 7 with a thickness of 50 mm. Although the Asker F hardness of each layer of Experimental Example 7 was lower than the Asker F hardness of the layer at the same position of Experimental Example 5, Experimental Example 7 also showed the characteristics of the first layer (F1) < the fifth layer (F5) < the third layer (F3) similarly to Experimental Example 5. This result suggests that the technology disclosed in the present disclosure is also effective for thin seat pads.

[0243] Experimental Example 4 was compared with Experimental Example 8 having a lower density than Experimental Example 4. Although the Asker F hardness of each layer of Experimental Example 8 was slightly lower than the Asker F hardness of the layer at the same position of Experimental Example 4, Experimental Example 8 also showed the characteristics of the first layer (F1) < the fifth layer (F5) < the third layer (F3) similarly to Experimental Example 4. This result suggests that the technology disclosed in the present invention is also effective for a low-density seat pad.

[0244] Experimental Example 5 with an isocyanate index of 105, Experimental Example 3 with an isocyanate index of 85, and Experimental Example 10 with an isocyanate index of 95 were compared. The first layer / third layer (F1 / F3) of Experimental Example 3 was 0.750. The first layer / third layer (F1 / F3) of Experimental Example 10 was 0.651. The first layer / third layer (F1 / F3) of Experimental Example 5 was 0.493. This result suggests that the larger the isocyanate index, the more the softness of the surface can be improved.

[0245] Experimental Example 5 and Experimental Example 9, which have different polyol mixing ratios, are compared. The polyol ratio of Experimental Example 5 is polyol a: polyol b = 85:15. The polyol ratio of Experimental Example 9 is polyol a: polyol b = 60:40. Although the Asker F hardness of each layer of Experimental Example 9 is greater than the Asker F hardness of the layer at the same position of Experimental Example 5, Experimental Example 9 also shows the characteristics of the first layer (F1) < fifth layer (F5) < third layer (F3) in the same manner as Experimental Example 5. In addition, the stress relaxation rate of Experimental Example 5 is 7.7%, which is less than the stress relaxation rate of Experimental Example 9, 18.4%. This result suggests that the greater the content of polyol a, the more durability can be improved.

[0246] In addition, the following inventions can also be understood from the above-mentioned experimental examples. The above-mentioned respective descriptions are appropriately cited for the description of specific matters of the following inventions.

[0247] A polyurethane foam obtained from a composition containing a polyol and an isocyanate, wherein the polyol contains 50 mol % or more of ethylene oxide units when the total amount of alkylene oxide units is 100 mol %, and the isocyanate index of the composition is 97 or more.

[0248] A polyurethane foam obtained from a composition containing a polyol and an isocyanate, wherein the polyol is a polyol containing 50 mol% or more of ethylene oxide units when the total amount of alkylene oxide units is 100 mol%, and satisfies at least one of the above requirements e, f, g, h and i.

[0249] 5. Result 2

[0250] Experimental Example 3-10 satisfies requirements a and f.

[0251] Requirement a: The seat pad is made of a polyurethane foam obtained from a composition containing a polyol and an isocyanate.

[0252] Requirement f: The compression deflection coefficient measured in accordance with JIS K6400-2 (2012 edition) Method E is 2.8 or less.

[0253] In addition, Experimental Example 1 did not satisfy requirement f. Experimental Examples 3-10 satisfying requirements a and f had good bending and less ground contact feeling than Comparative Example 1.

[0254] In addition, among the experimental examples 3 to 10, the experimental example 4 to 10 further satisfied the following requirement g. The experimental example 4 to 10 further satisfying the requirement g was excellent in riding comfort.

[0255] Requirement g: The rebound elasticity measured in accordance with JIS K6400-3 (2011 edition) is 55% or less.

[0256] In addition, among Experimental Examples 3-10, Experimental Examples 3-8 and 10 further satisfied the following requirement h. Experimental Examples 3-8 and 10 further satisfying the requirement h had good durability.

[0257] Requirement h: The stress relaxation rate is 15% or less.

[0258] In addition, among Experimental Examples 3 to 10, Experimental Examples 4-7 and 10 further satisfied the following requirement i. Experimental Examples 4-7 and 10 further satisfying the requirement i had good durability.

[0259] Requirement i: The hysteresis loss rate measured in accordance with JIS K6400-2 (2012 edition) Method E is 20% or less.

[0260] Experimental Example 5 with an isocyanate index of 105, Experimental Example 3 with an isocyanate index of 85, and Experimental Example 10 with an isocyanate index of 95 were compared. The compression deflection coefficients of Experimental Examples 3 and 10 were smaller than those of Experimental Example 5, and the deflection in the high load region (700 N or more and 980 N or less) was larger than that of Experimental Example 5.

[0261] Experimental Example 5, which satisfies requirements a and f, is compared with Experimental Example 1, which satisfies requirement a but does not satisfy requirement f. The 25% hardness of Experimental Example 5 is about 50N greater than that of Experimental Example 1, but the compression deflection coefficient is smaller than that of Experimental Example 1, and the deflection amount in the high load region (700N to 980N) is greater than that of Experimental Example 1.

[0262] Experimental Example 4 with 85 parts by mass of polyol a, Experimental Example 8 with 80 parts by mass of polyol a, and Experimental Example 9 with 60 parts by mass of polyol a were compared. It can be seen that as the amount of polyol a decreases, the compression deflection coefficient increases, and the deflection amount in the high load region (700 N or more and 980 N or less) decreases.

[0263] 6. Effects of the Embodiments

[0264] According to the above embodiments, a seat pad with excellent riding comfort can be provided.

[0265] The present disclosure is not limited to the embodiments described in detail above, and various modifications or changes can be made within the scope of the present disclosure.

[0266] Description of Reference Numerals

[0267] 10, 110: Seat cushion,

[0268] 10A: Front,

[0269] 10B: Back,

[0270] 11: First floor,

[0271] 12: Second floor,

[0272] 13: The third floor,

[0273] 14: The fourth floor,

[0274] 15: The fifth floor.

Claims

1. A seat cushion made of polyurethane foam obtained from a composition containing polyol and isocyanate, wherein: The compression deflection coefficient measured in accordance with JIS K6400-2 (2012 edition) E method is 2.8 or less.

2. A seat cushion made of polyurethane foam obtained from a composition containing polyol and isocyanate, wherein: As the polyol, when the total amount of alkylene oxide units is 100 mol %, the polyol contains a polyol having an ethylene oxide unit content of 50 mol % or more, The front side and the back side are divided into five equal parts in the thickness direction, and the first layer, the second layer, the third layer, the fourth layer, and the fifth layer are sequentially provided from the front side. When the Asker F hardness of the third layer measured from the front side is F3 and the Asker F hardness of the first layer measured from the front side is F1, Satisfy F1 / F3<1.

0.

3. The seat pad according to claim 2, wherein: Satisfies 0.30≤F1 / F3≤0.

70.

4. The seat pad according to claim 2 or 3, wherein: The isocyanate contains carbodiimide-modified diphenylmethane diisocyanate.

5. The seat pad according to any one of claims 2 to 4, wherein: The compression deflection coefficient measured in accordance with JIS K6400-2 (2012 edition) E method is 2.8 or less.

6. The seat pad according to any one of claims 2 to 5, wherein: The rebound elasticity measured in accordance with JIS K6400-3 (2011 edition) is 55% or less.

7. The seat pad according to any one of claims 2 to 6, wherein: The stress relaxation rate is 15% or less.

8. The seat pad according to any one of claims 2 to 7, wherein: The hysteresis loss rate measured in accordance with JIS K6400-2 (2012 edition) Method E is 20% or less.

Citation Information

Patent Citations

  • Cushion material for seat and seat

    JP2019107933A

  • Cushion material for seat and seat

    JP2022039004A

  • Metal surface coating film formation composition including hydroxy group containing polymer

    JP2022108852A

  • Method for producing fluororesin particles containing fluorine-containing alicyclic structure

    JP2022179573A

Cited By

  • Sponge for airplane cushion and preparation method thereof

    CN121203114A